Nanoemulsion and Multilayer Nanoemulsion Encapsulated with Chitosan Improving The Stability and Bioaccessibilty of Curcumin - Alwani Hamad; Afwa Hayuningtyas; Bekti Wulan Sari; Mubshair Naveed (Journal of Chemical Process and Material Technology, 2023)
Encapsulating lipophilic curcumin improves digestibility and bioavailability. Loading efficiency and droplet size are crucial when encapsulating curcumin into emulsion-based delivery systems. Since the thickness of the emulsifier layer is comparable to that of the radius of the oil droplet, one can deduce that the emulsifier layer is the primary component of the droplet's overall composition. Because the oil droplet radius matches the emulsifier layer thickness. Nanoemulsion (NE) is ideal for encapsulating, protecting, and delivering lipophilic nutraceuticals for food and food-related applications. Conventional emulsion has several-micrometer droplets. Chitosan-coated NE can deliver lipophilic bioactive substances. This is because it will better protect the core material. Phase separation was observed in the NE emulsion sample after it had been stored for three months, in contrast to the CNE emulsion sample. Multilayered emulsion is a multistep procedure that consists of emulsion droplets electrostatically stabilized by layers of alternatively charged emulsifiers and chitosan. The large surface area of nanoemulsions allows the acceleration of the chemical reactions occurring at the oil-water interface such as hydrolysis by lipases. There was a study that investigated the effect of nanosystems' interfacial composition using multilayer chitosan on the stability of curcumin during in vitro digestion, on lipids digestibility, cumin bioaccessibility and antioxidant activity, using a dynamic GI system.